Tuberculosis Exposure from a Healthcare Worker to Patients in a Neonatal Intensive Care Unit (NICU). (29th June 2022) - Casalino, Maria; Jegathesan, Thivia; Sgro, Michael; Rea, Elizabeth; Muller, Matthew; Campbell, Douglas M.
Abstract : The nosocomial spread of Mycobacterium tuberculosis from a healthcare worker with infectious pulmonary tuberculosis disease to patients remains a risk in the healthcare environment, including neonatal intensive care units. In this paper, we outlined a protocol for neonates exposed to tuberculosis in a neonatal intensive care unit that includes skin testing, chest X-ray imaging, and prophylactic isoniazid. Neonatal patients were followed up with tuberculosis skin testing at both three months corrected age and two months postexposure. To our knowledge, this is the first Canadian study to illustrate a protocol following tuberculosis exposure in a neonatal intensive care unit for exposed neonates.